Tropical Oral Disease: Analysing Barriers, Burden, Nutrition, Economic Impact, and Inequalities - Rajendra Santosh, Arvind Babu; Jones, Thaon (Frontiers in Nutrition, 2021)
Traditionally, a healthy mouth is a good indicator of good general health. Poor oral hygiene does not necessarily represent the health status of oral cavity but also reflects as a risk factor for overall health. Although oral diseases like dental decay, periodontitis are prevalent, awareness of oral diseases is still limited. Oral disorders include a wide range of diseases which may not be confined to the oral anatomical structures but may be manifestations of systemic diseases. Identification of the risk factors of the dental and oral diseases including socio-economic determinants, plays a major role in oral health care and in the promotion of dental health awareness. This article reviews oral diseases in the Caribbean and aims to raise the awareness of this subject while suggesting research agenda in the region.